President's page: ASPC is leading the way in preventive cardiology - Peter P. Toth (Elsevier, 2022)
It is hard for me to believe that my two-year term as president of the American Society for Preventive Cardiology (ASPC) will conclude in just 4 months. My objective over the last two years has been to make ASPC a major driving force and leader in the field of preventive cardiology. Although my time as president will conclude shortly, I will continue to make sure these goals are brought to fruition by satisfying goals and milestones I set at the start of my presidency, and by helping the leadership coming forward to achieve their goals as well. My only regret is that the COVID-19 pandemic made me unable to interact with so many of our valuable members. Hopefully, I will still meet many of you at the Annual Meeting in Louisville this July which will be held live.